The Value of a Thousand Suluks as a Foundation for MSME Taxpayer Compliance Registered in Rokan Hulu Regency - Nurhayati, Nurhayati; Sembiring, Boy Jerry (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2023)
Research objectives foranalyze the effect of Tax Morale and Taxpayer's Religious Value Simultaneously on MSME Taxpayer Compliance registered in Rokan Hulu Regency.Quantitative research is a research method based on positive philosophy, used to examine certain populations or samples, data collection uses research instruments, data analysis is quantitative/statistical in nature, with the aim of testing established hypotheses.the determined sample method is not random (non-probability sampling) with a sampling technique that is purposive sampling of 67 samples. The results of the study show that taxation morale has a significant effect on taxpayer compliance,Religious Value has a significant effect on taxpayer compliance and Tax Morale and Religious Value simultaneously have a significant effect on taxpayer compliance.